Erysipelothrix Spp.: Past, Present, and Future Directions in Vaccine Research - Opriessnig, Tanja; Forde, Taya; Shimoji, Yoshihiro (Frontiers in Veterinary Science, 2020)
Erysipelothrix spp. comprise a group of small Gram-positive bacteria that can infect a variety of hosts including mammals, fish, birds, reptiles and insects. Among the eight Erysipelothrix species that have been described to date, only E. rhusiopathiae plays a major role in farmed livestock where it is the causative agent of erysipelas. E. rhusiopathiae also has zoonotic potential and can cause erysipeloid in humans with a clear occupational link to meat and fish industries. While there are 28 known Erysipelothrix serovars, over 80% of identified isolates belong to serovars 1 or 2. Vaccines to protect pigs against E. rhusiopathiae first became available in 1883 as a response to an epizootic of swine erysipelas in southern France. The overall vaccine repertoire was notably enlarged between the 1940s and 1960s following major outbreaks of swine erysipelas in the Midwest USA and have changed little since. Traditionally, E. rhusiopathiae serovar 1a or 2 isolates were inactivated (bacterins) or attenuated and these types of vaccines are still used today on a global basis. E. rhusiopathiae vaccines are most commonly used in pigs, poultry and sheep where the bacterium can cause considerable economic losses. In addition, erysipelas vaccination is also utilized in selected vulnerable susceptible populations, such as marine mammals in aquariums, which are commonly vaccinated at regular intervals. While commercially produced erysipelas vaccines appear to provide good protection against clinical disease, in recent years there has been an increase in perceived vaccine failures in farmed animals, especially in organic outdoor operations. Moreover, clinical erysipelas outbreaks have been reported in animal populations not previously considered at risk. This has raised concerns over a possible lack of vaccine protection across various production species. This review focuses on summarizing the history and the present status of E. rhusiopathiae vaccines, the current knowledge on protection including surface antigens, and also provides an outlook into future directions for vaccine development.